Distributed computing and internet technology : 13th International Conference, ICDCIT 2017, Bhubaneswar, India, January 13-16, 2017, Proceedings /: 13th International Conference, ICDCIT 2017, Bhubaneswar, India, January 13-16, 2017, Proceedings. ([2017]) - Unknown
No abstract available